Myocardial leptin transcription in feline hypertrophic cardiomyopathy. (June 2017) - Fonfara, Sonja; Kitz, Sarah; Hetzel, Udo; Kipar, Anja
Abstract: Leptin is an adipokine, which is in humans with cardiac disease suspected to be involved in myocardial remodeling and thrombus formation. In cats, however, it is not known whether leptin plays a role in cardiac disease, i.e. hypertrophic cardiomyopathy (HCM) and the presence of an atrial thrombus (AT). The objective of the study was therefore to establish whether leptin is transcribed in the feline myocardium and to compare myocardial leptin mRNA concentrations in cats with HCM with and without AT, and in cats without cardiac diseases. Myocardial samples from 15 cats with HCM (five of these with AT), and 12 cats without cardiac diseases were investigated for leptin mRNA expression using quantitative reverse transcriptase PCR, and the transcription levels were correlated with those obtained for a range of cytokines and remodeling parameters. Leptin mRNA expression was detected in the myocardium in all heart regions, with generally higher concentrations in the atria than in the ventricles. Cats with HCM exhibited higher atria and ventricular leptin transcription than cats without cardiac diseases, but reduced ventricular transcription levels in the presence of AT. A positive correlation between leptin, cytokine and remodeling marker transcription levels was observed. The present study shows that leptin is constitutively transcribed in the feline myocardium. The observed increase in leptin mRNA concentrations in the myocardium from cats with HCM and the reduction when an AT is present suggests varying gene activation in different stages of the disease and a potential involvement of leptin in the feline cardiac remodeling process. Highlights: Leptin is transcribed in the feline myocardium. Leptin mRNA concentrations are higher in the atria than the ventricles. Cardiac leptin transcription is higher in HCM cats than cats without heart disease. Cats with HCM and atrial thrombus exhibit reduced ventricular leptin transcription.